N-type MOF-based high-performance thermoelectric foam with ductility as well as preparation method and application of n-type MOF-based high-performance thermoelectric foam

By performing hydrothermal synthesis and polymer grafting on the nickel foam surface, n-type MOF-based high-performance thermoelectric foam with ductility is prepared, which solves the shortcomings of existing MOF-based thermoelectric materials in terms of n-type and flexibility, and realizes the realization of the requirements of n-type and flexibility of the existing MOF-based thermoelectric materials. High performance and flexibility combined thermoelectric materials.

CN119451533AActive Publication Date: 2025-02-14NANKAI UNIV

Patent Information

Application Number
CN202411393615.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-14
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing MOF-based thermoelectric materials are mainly concentrated on p-type materials, and most of them exist in powder form. There is a lack of research on n-type flexible MOF composite thermoelectric materials, which is difficult to meet the needs of wearable electronic products for high performance, flexibility and safety.

Method used

Hydrothermal synthesis method is used to form a porous coordination polymer monomer on the surface of the foam nickel foam, and the conductive polymer is grafted in a mixed solution of polyaniline and DMF to prepare an n-type MOF-based high-performance thermal foam with ductility.

Benefits of technology

The thermoelectric properties with high Seebeck coefficient, high conductivity, low thermal conductivity and high output power density are achieved, and have flexibility and ductility. They are suitable for various heat source surfaces, which are significantly better than existing n-type MOF-based thermoelectric materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451533A_ABST
    Figure CN119451533A_ABST
Patent Text Reader

Abstract

The invention relates to the field of MOF-based flexible thermoelectric materials, and discloses n-type MOF-based high-performance thermoelectric foam with ductility and a preparation method and application thereof, and the method comprises the following steps: dissolving 1, 3, 5-trimesic acid and copper acetate in a mixed solution of N, N-dimethylformamide, ethanol and deionized water to prepare a precursor solution; soaking foamed nickel in the precursor solution for hydrothermal reaction, then taking out, cleaning and drying to obtain a foamed nickel material with nickel-copper MOF uniformly grown on the surface; and soaking the foamed nickel material in a mixed solution of polyaniline and DMF (Dimethyl Formamide) so as to graft a conductive polymer on the surface and pore channels of the nickel-copper MOF, thereby obtaining the high-performance thermoelectric foam with ductility. The n-type MOF-based thermoelectric foam prepared by the invention has excellent ductility and thermoelectric performance, and also has the characteristics of metal plasticity, efficient thermoelectric performance and sensitivity to temperature change. The excellent thermoelectric performance and wide application scene of the material are far better than those of the currently reported n-type MOF-based thermoelectric material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of MOF-based flexible thermoelectric materials, and in particular to an n-type MOF-based high-performance thermoelectric foam with ductility, and a preparation method and application thereof. Background Art

[0002] In the era of smart electronics advancement, the development of self-powered flexible and wearable electronics is imperative. The human body, as a stable heat source, continuously radiates thermal energy. If this waste heat can be reasonably collected, it will generate huge economic benefits. Based on the Seebeck effect, thermoelectric materials can effectively convert waste heat generated by the human body or other heat sources into electrical energy, which is expected to provide a new strategy for the development of self-powered electronic products. At present, the most representative thermoelectric materials are inorganic semiconductor materials. However, the inherent rigid structure and toxicity of most inorganic thermoelectric materials make it difficult to meet the requirements of human safety and practical wearable applications. Therefore, in order to develop safe and reliable wearable thermoelectric devices, current research mainly focuses on the development of new materials and the composite research of organic and inorganic thermoelectric materials.

[0003] Metal-organic framework (MOF) materials have shown great potential in the field of thermoelectrics due to their high porosity and adjustable structure. Although most MOF materials are electrical insulators due to the low conjugation and poor orbital overlap between organic ligands and metal ions, the precise selection and arrangement of metal centers and organic ligands can effectively adjust the thermal and electrical properties. The combination of conjugated polymers and metal organic coordination polymers enables their electrical and thermal conductivity to meet the requirements of thermoelectric conversion. However, current research on MOF thermoelectric materials mainly focuses on p-type materials, and most MOF-based thermoelectric materials exist in the form of powders. There are few reports on n-type flexible MOF composite thermoelectric materials. Therefore, it is necessary to develop an n-type MOF-based thermoelectric foam with high Seebeck coefficient, high electrical conductivity, low thermal conductivity, high output power density, and the ability to adapt to various heat source surfaces and ductility, so as to generate electricity using temperature response and drive low-power wearable sensing electronic devices. Summary of the invention

[0004] Based on the above technical problems, the present invention provides a ductile n-type MOF-based high-performance thermoelectric foam and a preparation method and application thereof.

[0005] To achieve the above purpose, on the one hand, the present invention provides a ductile n-type MOF-based high-performance thermoelectric foam, which uses nickel foam (NF) as a matrix, connects the Cu (II) ions and a small amount of free Ni (II) in the precursor solution with the four oxygen atoms of 1,3,5-benzenetricarboxylic acid (BTC) ligands by hydrothermal synthesis, and forms a porous coordination polymer monomer with a face-centered cubic crystal structure on the surface of nickel foam; then, it is immersed in a mixed solution of polyaniline and N,N-dimethylformamide (DMF), and cross-linked with polyaniline (PANI) molecules to interpenetrate and graft conductive polymers on the MOF surface and pores. The specific preparation steps are as follows:

[0006] S1. Dissolve 1,3,5-benzenetricarboxylic acid (BTC) and copper acetate (Cu(OAc)2·H2O) in a mixed solution of N,N-dimethylformamide (DMF), ethanol (EtOH) and deionized water (DI) to prepare a precursor solution.

[0007] S2, immersing nickel foam (NF) in the precursor solution of step S1 to perform a hydrothermal reaction, and then taking it out, washing it, and drying it to obtain a nickel foam material with nickel-copper MOF uniformly grown on the surface;

[0008] S3, soaking the nickel foam material in step S2 in a mixed solution of polyaniline (PANI) and DMF to graft a conductive polymer on the surface and pores of the nickel-copper MOF, thereby obtaining a high-performance thermoelectric foam with ductility.

[0009] As a further preferred technical solution of the present invention, before step S2, it also includes a pretreatment step of the nickel foam by soaking in acetone, hydrochloric acid and ethanol respectively.

[0010] As a further preferred technical solution of the present invention, in the precursor solution of step S1, the addition amount of 1,3,5-trimethylbenzenecarboxylic acid is 10.0-50.0 mmol / L, and the addition amount of copper acetate is 0.1-50.0 mmol / L.

[0011] As a further preferred technical solution of the present invention, in step S1, the volume ratio of N,N-dimethylformamide, ethanol and deionized water is 1:1:1.

[0012] As a further preferred technical solution of the present invention, in step S2, a Teflon reactor is used to carry out a hydrothermal reaction.

[0013] As a further preferred technical solution of the present invention, in step S2, the temperature for the hydrothermal reaction is 100-150° C. and the time is 10-20 h.

[0014] As a further preferred technical solution of the present invention, in step S3, polyaniline is added to N,N-dimethylformamide at a concentration of 1.0-4.0 g / L, and ultrasonicated for 20-60 minutes to form a mixed solution.

[0015] As a further preferred technical solution of the present invention, in step S3, the soaking temperature is 50-80°C, and the soaking time is 2-6h.

[0016] According to another aspect of the present invention, the present invention also provides an n-type MOF-based high-performance thermoelectric foam, which is prepared by the above method.

[0017] According to another aspect of the present invention, the present invention also provides an n-type MOF-based high-performance thermoelectric foam for use as a flexible semiconductor material in the field of thermoelectric conversion in temperature difference power generation on the surface of a heat source, and further applied to wearable sensing devices or self-powered wearable electronic devices. Based on the plasticity of the thermoelectric foam, it can be applied to any regular heat source surface.

[0018] The present invention uses nickel foam as a matrix, connects the Cu(II) ions and a small amount of free Ni(II) in the precursor solution with the four oxygen atoms of the BTC ligand by a hydrothermal synthesis method, and forms a porous coordination polymer monomer with a face-centered cubic crystal structure on the surface of the nickel foam; then soaks it in a mixed solution of polyaniline and DMF, takes it out and washes it, and then obtains the ductile MOF-based thermoelectric foam of the present invention. This synthesis strategy customizes the electrical and thermal properties through the adjustability of the mixed material, and combines the superior performance of inorganic materials, nanostructure geometry and organic materials, thereby providing a powerful way to enhance thermoelectric performance.

[0019] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0020] 1) The present invention adopts a hydrothermal synthesis and polymer grafting strategy, and its preparation method is simple and easy, and has the potential for mass production.

[0021] 2) The n-type MOF-based thermoelectric foam prepared by the present invention has excellent ductility and thermoelectric properties. The NCM@PANI / NF thermoelectric foam also has the characteristics of metal plasticity, high-efficiency thermoelectric performance and sensitivity to temperature changes. Its excellent thermoelectric performance and wide application scenarios are far superior to the currently reported n-type MOF-based thermoelectric materials. For example, the Seebeck coefficient of the currently studied n-type Cu-MOF materials is concentrated in the range of -10 to -30 μV / K, which is lower than that of the present invention, and it is difficult to apply to complex heat source surfaces without plasticity.

[0022] 3) The n-type MOF-based thermoelectric foam prepared by the present invention has ductility, so that the design of the thermoelectric device can match heat sources of different specific shapes, and the practicality is better.

[0023] 4) The present invention can prepare various ductile thermoelectric devices based on n-type MOF-based thermoelectric foam, which has good application prospects in the fields of temperature difference power generation, intelligent thermal management, and thermoelectric wearables. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0025] Figure 1 The optical photographs of the thermoelectric foam prepared in Example 1 and the partially enlarged scanning electron microscope photographs thereof, wherein a is an optical photograph of synthesized thermoelectric foams of different sizes; b is a partially enlarged scanning electron microscope photograph of NCM / NF; c is a partially enlarged scanning electron microscope photograph of NCM@PANI / NF;

[0026] Figure 2 The energy dispersive X-ray spectrum of the NCM@PANI / NF thermoelectric foam prepared in Example 1;

[0027] Figure 3 The ductility bending performance and thermoelectric performance of the thermoelectric foam prepared in Example 1, wherein a is an optical picture of the ductility bending of the thermoelectric foam, and b is the Seebeck coefficient at different folding and bending degrees;

[0028] Figure 4 The thermoelectric performance of the thermoelectric foam in Example 1 at different temperature differences, Figure 4 The voltage-current density and output power density curves under different temperature differences;

[0029] Figure 5 The Seebeck coefficient and conductivity change curve of the thermoelectric foam prepared in Comparative Example 1 optimized in Cu(OAc)2·H2O precursor solutions with different contents;

[0030] Figure 6Comparison of the Seebeck coefficient and conductivity of NCM@PANI / NF, NCM / NF-0.5, NM / NF and pure nickel foam;

[0031] Figure 7 This is the NCM@PANI / NF thermoelectric array device made by using a surrounding tubular heat source with the thermoelectric foam (thickness 1.7 mm) in Example 1, where a is the optical image and schematic diagram, and b is its output voltage and power.

[0032] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0033] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0034] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0035] The test methods involved in the following embodiments and comparative examples are: using a self-built test device to test the Seebeck coefficient of the thermoelectric foam; using a low-voltage power supply and a commercial Peltier heating module to control the temperature difference between the left and right ends of the sample, using a Keithley 2450 data acquisition system to measure the open circuit voltage at both ends of the thermoelectric foam, and using a thermocouple to measure the real-time temperature at both ends of the thermoelectric foam to obtain the temperature difference and calculate the Seebeck coefficient. The thermoelectric foam designed in the embodiment of the present invention has an effective length of 40 mm and a width of 10 mm. Copper wires are connected to both ends of the thermoelectric foam as electrodes. Keithley 2450 is used to measure the resistance at both ends of the thermoelectric foam. According to the length, resistance, and cross-sectional area of ​​the thermoelectric foam, its resistivity is calculated and converted into conductivity.

[0036] Embodiment 1:

[0037] The preparation method of the thermoelectric foam and device provided in this embodiment is as follows:

[0038] (1) A 1.7 mm thick nickel foam material was cut into 2 cm × 2 cm pieces, and soaked in acetone, hydrochloric acid, and ethanol for 15 min, respectively, and the surface oil and oxide layer were removed by ultrasonic treatment.

[0039] (2) 2.5 mmol of 1,3,5-tricarboxylic acid benzene (BTC) and 0.5 mmol of Cu(Ac)2·H2O were dissolved in 75 mL of a mixed solution of DMF:DI:EtOH (1:1:1) and stirred for 10 min to obtain a precursor solution;

[0040] (3) The nickel foam (2 cm×2 cm) pretreated in step (1) was immersed in the precursor solution of step (2), and the whole was transferred to a 100 ml Teflon reactor, and reacted in an oven at 120° C. for 16 h, and then cooled to room temperature.

[0041] (4) The sample obtained in step (3) was rinsed with deionized water and anhydrous ethanol, and then dried in a vacuum drying oven at 70° C. overnight to obtain a nickel foam material, which was recorded as NCM / NF;

[0042] (5) The nickel foam material was immersed in 200 mL of 2 g / L PANI / DMF dispersion solution, slowly stirred at 60 °C for 4 h, cooled to room temperature, rinsed with DMF and ethanol several times, and dried at 50 °C to obtain a thermoelectric foam, which was recorded as NCM@PANI / NF.

[0043] (6) The thermoelectric foam was cut into strips with a size of 40 mm × 10 mm × 1.7 mm, and copper wires were used as electrodes to connect the left and right ends to obtain the corresponding thermoelectric foam device.

[0044] In order to further verify the feasibility of the present invention, based on Example 1, thermoelectric foams of different thicknesses were prepared under the same process. The obtained samples are as follows: Figure 1 As shown. Figure 1 It can be seen from a that thermoelectric foam can be synthesized using nickel foam substrates of different thicknesses (20 mm, 10 mm, 5.0 mm, and 1.7 mm). Figure 1 b It can be seen that NiCu-MOF with typical morphology is uniformly formed on the surface of NCM / NF, with a lateral size between 5 and 10 μm and an octahedral structure. Figure 1 c It can be seen that NCM@PANI / NF is uniformly coated by PANI with rough surface.

[0045] Figure 2 The energy dispersive X-ray spectrum of NCM@PANI / NF in Example 1 is shown, and the Ni, Cu and C elements are uniformly distributed on NCM / NF, indicating that there is uniform substitution between Cu and Ni.

[0046] Figure 3 This is a bending demonstration of the ductility of the thermoelectric foam prepared in Example 1. Figure 3 a It can be seen that the prepared thermoelectric foam can be twisted into different shapes. Figure 3b is the folding bending test of the plastic ductility of TE foam. After NCM@PANI / NF was bent at different bending radii, the Seebeck coefficient did not change significantly. The cross-linking protection of NiCu-MOF by polyaniline polymer can inhibit the internal structure fracture caused by bending or folding. This means that NCM@PANI / NF thermoelectric materials have significant ductility and shape adaptability, so that in their applications, different shapes can be shaped according to actual needs.

[0047] Figure 4 In order to optimize the thermoelectric performance of the thermoelectric foam under different temperature differences in Example 1, the temperature differences are 8K, 12K, 15K, 20K and 25K respectively. It can be seen that with the increase of the temperature difference, the maximum output power density of the thermoelectric foam also gradually increases, and the corresponding maximum output power density gradually increases from 205.83μW·m-2 to 696.04μW·m-2.

[0048] Comparative Example 1:

[0049] As a comparative experiment of Example 1, the difference is that the immersion step of PANI / DMF dispersion solution is omitted, and the addition amount of Cu(Ac)2·H2O is changed to 0.1mmol, 0.5mmol, 1mmol, and 2mmol respectively. The specific steps are as follows:

[0050] (1) The nickel foam raw material was cut into small pieces of 2 cm × 2 cm, and soaked in acetone, hydrochloric acid and ethanol for 15 min respectively, and the surface oil and oxide layer were removed by ultrasonic.

[0051] (2) 2.5 mmol 1,3,5-tricarboxylic acid (BTC) and x mmol Cu(Ac)2·H2O were dissolved in 75 mL DMF:DI:EtOH (1:1:1) mixed solution and stirred for 10 min, where x is 0.1, 0.5, 1 or 2;

[0052] (3) The nickel foam (2 cm×2 cm) pretreated in step (1) was immersed in the mixed solution and transferred as a whole to a 100 ml Teflon reactor. After reacting for 16 h in an oven at 120° C., the reaction was cooled to room temperature.

[0053] (4) The sample obtained in step (3) was rinsed with deionized water and anhydrous ethanol, and then dried in a vacuum drying oven at 70° C. overnight to obtain a thermoelectric foam without grafted conductive polymer. The thermoelectric foam samples with different amounts of Cu(Ac)2·H2O added were labeled NCM-x, where x was 0.1, 0.5, 1, and 2, respectively.

[0054] (5) The thermoelectric foam is cut into strips with a size of 40 mm × 10 mm × 1.7 mm, and copper wires are used as electrodes to connect the left and right ends to obtain the corresponding thermoelectric foam device.

[0055] Figure 5 The changes in the Seebeck coefficient and conductivity of the thermoelectric foam caused by the use of different contents of Cu(OAc)2·H2O in Example 2 are shown. It can be seen that as the addition amount of Cu(OAc)2·H2O in NCM / NF increases from 0.1 to 2 mmol, the Seebeck coefficient first increases and then decreases, while the conductivity increases from 136.7 to 179.71 S·m -1 In Cu 2+ The content is 0.5mmol (NCM / NF-0.5), and the Seebeck coefficient is -38.2μV·K -1 , the conductivity is 158.83S·m -1 .

[0056] Comparative Example 2

[0057] The only difference from Comparative Example 1 is that the amount of Cu(Ac)2·H2O added is 0. The specific steps are as follows:

[0058] (1) The nickel foam was cut into small pieces of 2 cm × 2 cm and soaked in acetone, hydrochloric acid and ethanol for 15 min respectively, and the surface oil and oxide layer were removed by ultrasonic treatment.

[0059] (2) Dissolve 2.5 mmol of 1,3,5-trimethylbenzenecarboxylic acid (BTC) in 75 mL of a DMF:DI:EtOH (1:1:1) mixed solution and stir for 10 min;

[0060] (3) The nickel foam (2 cm×2 cm) pretreated in step (1) was immersed in the mixed solution and transferred as a whole to a 100 ml Teflon reactor. After reacting for 16 h in an oven at 120° C., the reaction was cooled to room temperature.

[0061] (4) The sample obtained in step (3) was rinsed with deionized water and anhydrous ethanol, and then dried in a vacuum drying oven at 70° C. overnight to obtain a thermoelectric foam, which was recorded as NM / NF.

[0062] (5) The thermoelectric foam is cut into strips with a size of 40 mm × 10 mm × 1.7 mm, and copper wires are used as electrodes to connect the left and right ends to obtain the corresponding thermoelectric foam device.

[0063] The Seebeck coefficient of the NM / NF prepared in Comparative Example 2 is -33.7 μV·K-1, the electrical conductivity is 136.7 S·m-1, and the thermal conductivity is 0.070 W·m-1K-1.

[0064] Figure 6The electrical properties of the three thermoelectric foams prepared in Example 1, Comparative Example 1 and Comparative Example 2 and the pure nickel foam are compared, showing the Seebeck coefficient and conductivity change curves of the four materials. Figure 5 It can be seen that the introduction of 0.5mmol Cu(OAc)2·H2O into the precursor solution significantly improves the Seebeck coefficient and conductivity of the thermoelectric foam. In addition, the grafting of polyaniline greatly improves the Seebeck coefficient and conductivity of the thermoelectric foam. The Seebeck coefficient of NCM@PANI / NF is -53.1μV·K -1 , conductivity is 872.39S·m -1 , and its comprehensive performance is much higher than that of the currently reported MOF-based n-type thermoelectric materials.

[0065] Figure 7 This is a NCM@PANI / NF thermoelectric array device made of the thermoelectric foam prepared in Example 1. The thermoelectric foam is bent into a semicircular arc shape and fixed on the surface of the flexible Ecoflex strip. Then, the cylindrical device is wrapped on the tubular heat source. One side of the cylindrical thermoelectric array directly contacts the heat source as the hot side, and the other side is exposed to the air as the cold side. Hot water of different temperatures is passed into the steel pipe with good thermal conductivity so that the surface temperature of the pipe is maintained at about 30, 50, 70 and 90°C. The electrical signals generated by the thermoelectric array device under different temperature differences are measured by a digital multimeter (Keithley 2450 system). Under the final stable conditions, when the surface temperature of the pipe is about 30, 50, 70 and 90°C, the corresponding maximum output powers are 0.21, 1.33, 3.55 and 6.43μW, respectively. These results further reflect the great advantages of NCM@PANI / NF thermoelectric foam in ductility and shape consistency in the fields of thermal energy collection and flexible electronics.

[0066] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a ductile n-type MOF-based high-performance thermoelectric foam, characterized in that: The following steps are involved: S1, dissolving 1,3,5-trimethylbenzene trimesic acid and copper acetate in a mixed solution of N,N-dimethylformamide, ethanol and deionized water to prepare a precursor solution; S2, immersing the nickel foam in the precursor solution of step S1 to perform a hydrothermal reaction, and then taking it out, washing, and drying it to obtain a nickel foam material with nickel-copper MOF uniformly grown on the surface; S3, soaking the nickel foam material of step S2 in a mixed solution of polyaniline and N,N-dimethylformamide to graft a conductive polymer on the surface and pores of the nickel-copper MOF, thereby obtaining a high-performance thermoelectric foam with ductility.

2. The method for preparing a ductile n-type MOF-based high-performance thermoelectric foam according to claim 1, characterized in that: Before step S2, the method further includes soaking the nickel foam in acetone, hydrochloric acid and ethanol respectively to achieve a pretreatment step for the nickel foam.

3. The method for preparing a ductile n-type MOF-based high-performance thermoelectric foam according to claim 1, characterized in that: In the precursor solution of step S1, the addition amount of 1,3,5-trimethylbenzenecarboxylic acid is 10.0-50.0 mmol / L, and the addition amount of copper acetate is 0.1-50.0 mmol / L.

4. The method for preparing a ductile n-type MOF-based high-performance thermoelectric foam according to claim 1, characterized in that: In step S1, the volume ratio of N,N-dimethylformamide, ethanol and deionized water is 1:1:

1.

5. The method for preparing a ductile n-type MOF-based high-performance thermoelectric foam according to claim 1, characterized in that: In step S2, a Teflon reactor is used to carry out a hydrothermal reaction.

6. The method for preparing a ductile n-type MOF-based high-performance thermoelectric foam according to claim 1, characterized in that: In step S2, the temperature for the hydrothermal reaction is 100-150° C. and the time is 10-20 hours.

7. The method for preparing a ductile n-type MOF-based high-performance thermoelectric foam according to claim 1, characterized in that: In step S3, polyaniline is added to N,N-dimethylformamide at a concentration of 1.0-4.0 g / L, and ultrasonicated for 20-60 min to form a mixed solution.

8. The method for preparing a ductile n-type MOF-based high-performance thermoelectric foam according to claim 1, characterized in that: In step S3, the soaking temperature is 50-80°C, and the soaking time is 2-6 hours.

9. An n-type MOF-based high-performance thermoelectric foam, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Application of the n-type MOF-based high-performance thermoelectric foam according to claim 9 as a flexible semiconductor material for temperature difference power generation on any regular heat source surface in the field of thermoelectric conversion.

Citation Information

Patent Citations

  • Foam metal / bismuth telluride thermoelectric composite material

    CN114497338A

  • Preparation method of carbon-coated foamed nickel in-situ growth Ni3S2atCuS electrode material

    CN117894600A

  • Thermoelectrically active aerogel

    DE102013112522A1

  • Shaped MOF-based composite phase-change material, preparation method therefor and use thereof

    WO2021031976A1

  • Nickel-based MOF film photocatalyst grown in-situ on foamed nickel surface, preparation method therefor, and application thereof

    WO2021164539A1

Cited By

  • Heat-insulating moisture-proof thermoelectric device and preparation method thereof

    CN120302862A

  • A heat-insulating and moisture-proof thermoelectric device and its preparation method

    CN120302862B